2011
DOI: 10.1007/s13187-011-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development and the Informal Curriculum in End-of-Life Care

Abstract: Although professionalism has emerged as a key competency for today’s physicians, there exists little insight into how best to teach medical students the relevant skills or instill in them the commitment required to practice according to the highest professional standards. Ten UCSF medical students were interviewed at three time points (second, third, and fourth years of school). Interviews focused on students’ learning and development regarding end-of-life care (EOLC). Students described varying steps in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
(19 reference statements)
1
23
0
1
Order By: Relevance
“…The element identified as 'achieving medical professionalism' seems to be a recurring theme of the informal curriculum across both educational levels and disciplines [54][55][56][57][58][59]. Our study confirmed that in FM this is no exception.…”
Section: Findings In Relation To Previous Worksupporting
confidence: 76%
“…The element identified as 'achieving medical professionalism' seems to be a recurring theme of the informal curriculum across both educational levels and disciplines [54][55][56][57][58][59]. Our study confirmed that in FM this is no exception.…”
Section: Findings In Relation To Previous Worksupporting
confidence: 76%
“…The two‐stage screening process resulted in 92 studies included in the scoping review . Of these, 57 investigated PIF in medical students and/or residents, 26 involved nurse trainees (associate, bachelor, graduate and nurse managers), and nine involved counselling or psychology undergraduate or graduate students …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 57 investigated PIF in medical students and/or residents, 26 involved nurse trainees (associate, bachelor, graduate and nurse managers), and nine involved counselling or psychology undergraduate or graduate students . Three of the studies had a mixed‐methods design, six were quantitative and 83 were qualitative …”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] The minimal amount of palliative content in nurse practitioner programs may hinder the next generation of practitioners from developing skills to provide excellent palliative care if they believe it is not a valued part of their education. 23 This lack of exposure can have long-term effects. End-of-life care education is one of the most significant factors affecting nurses' knowledge, skills, and attitudes toward the care of those with life-limiting illness.…”
Section: Discussionmentioning
confidence: 99%